Person-environment fit and its impact on psychological strain: evidence from Malaysian banking system / Siti Nurul Akma Ahmad … [et al.] - Ahmad, Siti Nurul Akma; Abdul Rasid, Siti Zaleha; Abdul Rasool, Mohamed Saladin; Hashim, Azman (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The banking sector has played an important role as the major contributor to the economic stability in various countries. The failure of the banking sector may lead to financial disturbance and affect economic growth. Due to these reasons, the banking sector is a well-deserved industry to be further investigated. Besides, the changes in the banking system has resulted in tremendous stress at a critical level which in turn, has significantly impacted the workers’ health. Therefore, this study aims to measure the predictors of work-related stress by adapting the Person-Environment Fit Theory and its influence on psychological strain. The population of this study involved employees from seven banks in Kuala Lumpur using the purposive sampling technique to gather a total of 191 respondents as the study’s samples. The findings show that three out of four variables were found significant. The relationships of PJF a n dP SY ST (f = -0.038, p<0.001), PG F a n dP SY ST (f = -0.154, p=0.015), PSF and PSYST (f = -0.171, p=0.008) are all significant. This study sets a new direction for future studies investigating the health outcome of employee strain, by highlighting the match between person and environment as an important predictor of psychological strain.